Time for a Tailored Approach to South African BRTs : - Munoz-Raskin, Ramon; Scorcia, Harvey (World Bank, Washington, DC, 2017)
Johannesburg and other cities in South Africa are rolling out integrated rapid public transport networks as part of an overall effort to address significant urban mobility challenges and to increase the use of public transport.The initial phases of these networks used a traditional Bus Rapid Transit (BRT) trunk and feeder approach, patterned after the successful Latin American systems developed in the 2000s. The Rea Vaya BRT in Johannesburg is South Africa’s first such system, with 43.5 km of trunk bus corridors in operation by 2016. But the results in ridership and operating cost recovery from fares were approximately one-third of initial estimates. Urban form and travel demand patterns for transport in South African cities differ greatly from those in Latin America. South Africa’s national government, with World Bank support, has been examining these differences to reassess how South African metropolises could interpret and rethink their rapid transit operations, services, and finances.